Analisis Semiotik Derrida dalam Gaya Komunikasi Publik Dedi Mulyadi - Susanti, Ratna; Zulham, Zulham; Pranawukir, Iswahyu; Kusuma, Ema; Ningsih, Titiek Surya (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
This study aims to analyze Dedi Mulyadi’s public communication style through Derrida’s semiotics, particularly the concept of deconstruction. This approach is used to uncover layers of meaning often manifested by cultural narratives, traditional symbols, and cultural expressions on digital platforms. Using a qualitative method with text and video analysis, interpretation of symbols, diction, and gestures, the study reveals that Dedi Mulyadi’s communication is rich in markers of locality, simplicity, and closeness to the people. However, these meanings are not singular and remain open to deconstruction. Based on Derrida’s conception, it is found that Dedi Mulyadi’s communication style blurs the boundaries between the elite and the people, power and simplicity, representation and reality. His public communication style represents a deconstruction of conventional political communication practices by blending modern and traditional symbols, dissolving the boundary between the elite and the masses through the use of ambiguous yet populist. This approach also helps to reveal how the signs used by Dedi Mulyadi are highly open to multiple interpretations and continuously shifting meanings. The study recommends the importance of applying deconstructive analysis in political communication studies to better understand the dynamics of meaning and imagery within digital public spaces.